Aerobiology of the Asian soybean rust pathogen for monitoring inoculum dispersal and RT qPCR detection of the SdhC I86F substitution associated with resistance to SDHI fungicides in populations of Phakopsora pachyrhizi from Brazil - Krug, Loane Dantas [UNESP] (2024)
Asian soybean rust, caused by the fungus Phakopsora pachyrhizi (Pp), is the main disease affecting soybean production in Brazil, leading to significant losses and management costs estimated at approximately US$ 2 billion per crop. Since its introduction to Brazil in the 2001/2002 growing season, the disease has spread rapidly, affecting nearly all soybean-producing regions and consistently challenging farmers. The widespread resistance of the pathogen to fungicides, particularly to QoI, DMI, and SDHI groups, has compromised chemical control, necessitating new management strategies. This study focused on monitoring airborne populations of P. pachyrhizi in Londrina, Paraná, between 2019 and 2021, using a high-volume cyclone for air collection and quantitative real-time PCR (qPCR) for pathogen DNA detection. Sample analysis revealed the presence of P. pachyrhizi in 24.73% of samples, with significant peaks in March 2020 and 2021, coinciding with the critical grain-filling period. Climate variables, such as rainfall, relative humidity, and wind speed, showed significant correlations with the presence of pathogen DNA, with accumulated rainfall presenting a negative correlation, and relative humidity and wind speed showing positive correlations at certain periods. Furthermore, fungicide resistance has become an increasing concern. Resistance to QoI and DMI fungicides has reduced the efficacy of chemical control, while new SDHI fungicides have also faced resistance. The detection of the SdhC-I86F mutation, associated with SDHI resistance, was prevalent in populations sampled between 2020/21 and 2022/23 across various Brazilian states, confirming the persistence of this substitution. The analyses also showed that phenotyped populations had reduced sensitivity to the fungicide fluxapyroxad. The results highlight the effectiveness of the employed methodology for monitoring and detecting P. pachyrhizi and provide valuable information for more efficient management practices, which may help reduce dependence on fungicides and promote more sustainable agriculture.